Ocean Acidification Alters the Predator – Prey Relationship Between Hydrozoa and Fish Larvae - Spisla, Carsten; Taucher, Jan; Sswat, Michael; Wunderow, Hennrike; Kohnert, Peter; Clemmesen, Catriona; Riebesell, Ulf (Frontiers in Marine Science, 2022)
Anthropogenic CO2 emissions cause a drop in seawater pH and shift the inorganic carbon speciation. Collectively, the term ocean acidification (OA) summarizes these changes. Few studies have examined OA effects on predatory plankton, e.g. Hydrozoa and fish larvae as well as their interaction in complex natural communities. Because Hydrozoa can seriously compete with and prey on other higher-level predators such as fish, changes in their abundances may have significant consequences for marine food webs and ecosystem services. To investigate the interaction between Hydrozoa and fish larvae influenced by OA, we enclosed a natural plankton community in Raunefjord, Norway, for 53 days in eight ≈ 58 m³ pelagic mesocosms. CO2 levels in four mesocosms were increased to ≈ 2000 µatm pCO2, whereas the other four served as untreated controls. We studied OA-induced changes at the top of the food web by following ≈2000 larvae of Atlantic herring (Clupea harengus) hatched inside each mesocosm during the first week of the experiment, and a Hydrozoa population that had already established inside the mesocosms. Under OA, we detected 20% higher abundance of hydromedusae staged jellyfish, but 25% lower biomass. At the same time, survival rates of Atlantic herring larvae were higher under OA (control pCO2: 0.1%, high pCO2: 1.7%) in the final phase of the study. These results indicate that a decrease in predation pressure shortly after hatch likely shaped higher herring larvae survival, when hydromedusae abundance was lower in the OA treatment compared to control conditions. We conclude that indirect food-web mediated OA effects drove the observed changes in the Hydrozoa – fish relationship, based on significant changes in the phyto-, micro-, and mesoplankton community under high pCO2. Ultimately, the observed immediate consequences of these changes for fish larvae survival and the balance of the Hydrozoa – fish larvae predator – prey relationship has important implications for the functioning of oceanic food webs.